Benny uncovers a mystery - Warner, Gertrude Chandler, 1890-; Cunningham, David, 1938- (Chicago : A. Whitman, 1976)
Two brothers take summer jobs at a department store where a series of peculiar events brings them under suspicion.
School Library Journal
4.8
3-6
Keywords: Mystery and detective stories; Mystery fiction